ANALYTICAL HIERARCHY PROCESS IN DETERMINING LEVEL THE FEASIBILITY OF THE AUTOMATED TELLER MACHINE LOCATION (CASE STUDY BANK SYARIAH INDONESIA JEMBER) - Pradjaningsih, Agustina; Anggraeni, Dyan Mei; Santoso, Kiswara Agung (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2022)
Bank Syariah Indonesia (BSI) is a new Islamic bank resulting from the merger of three Islamic banks that requires development to maximize the feasibility of the Automated Teller Machine (ATM) location. The placement of a proper ATM location can increase the bank's profits. This research was conducted to assist BSI Jember Regency in determining the feasibility level of 10 ATM locations that are already owned based on several criteria that have been selected. This study aims to analyze the results of the feasibility of the BSI ATM location. The method used in this study is the Analytical Hierarchy Process (AHP) method. AHP is a method used to rank an alternative decision best from several criteria that must be met or considered. In this study, four criteria and ten alternatives were used. These criteria are the distance of the ATM from the center of the crowd (X1), the distance of the ATM from the security office (X2), the number of residents (X3), and the number of non-BSI ATMs (X4), while the alternative is 10 BSI ATM locations. This study obtained the results of the feasibility of the location of the establishment of 10 BSI ATMs, with the BSI KKAS UNMUH ATM, which ranked first because it had the most considerable value of 0.1674.